2004
DOI: 10.1002/srin.200405927
|View full text |Cite
|
Sign up to set email alerts
|

Iron Aluminium Alloys with Strengthening Carbides and Intermetallic Phases for High-Temperature Applications

Abstract: An overview of materials developments of iron aluminium alloys with strengthening precipitate phases is given. The discussion is focussed on recent studies on Fe-AI-based alloys with strengthening precipitates, such as x-phase Fe~ICx, MC-carbide and Laves phase. Alloys of the following alloy systems were investigated: Fe-AI-C, Fe-AI-Ta, Fe-AI-Ni, Fe-AI-Ti-Nb, and Fe-AI-M-C (M = Ti, V, Nb, Ta). The investigations were centred on microstructure, constitution, and mechanical properties of such Fe-AI-based alloys … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…In a second contribution by the same authors the strengthening in Fe-Al-M-C (MZTi, V, Nb, Ta) alloys by carbides and additional Laves phase has been studied [69]. Preliminary results of both studies have also been reported in [70].…”
Section: Precipitates Of Carbidesmentioning
confidence: 96%
“…In a second contribution by the same authors the strengthening in Fe-Al-M-C (MZTi, V, Nb, Ta) alloys by carbides and additional Laves phase has been studied [69]. Preliminary results of both studies have also been reported in [70].…”
Section: Precipitates Of Carbidesmentioning
confidence: 96%
“…For Fe 3 Al based alloys it was demonstrated that precipitates such as carbides, borides and Laves phase are useful for strengthening [7][8][9]. Recent investigations revealed that the precipitates are effective for strengthening also at very high temperatures around 800 8C [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Serious problems are the limited ductility at low temperatures and the poor high-temperature strength and creep resistance. However, many investigations performed during the last two decades [3][4][5][6][7][8][9][10][11][12][13] have led to the improvement of each individual property. It is now the matter to combine these results and to optimise the fabrication processes for a novel Fe 3 Al based alloy with improved properties.…”
Section: Introductionmentioning
confidence: 99%
“…Further strengthening may be achieved by ternary alloying which stabilises atomic ordering to higher temperatures, provides solid solution hardening and produces additional precipitate hardening [21,22]. A major project was performed to clarify the phase relations and equilibria in the ternary Fe -Al-Mo system and to screen the deformation characteristics of Fe -Al-base alloys with hardening intermetallic phases in this system.…”
Section: Introductionmentioning
confidence: 99%